2007
DOI: 10.1109/iembs.2007.4352606
|View full text |Cite
|
Sign up to set email alerts
|

Model-based measurement of epileptic tissue excitability

Abstract: In the context of pre-surgical evaluation of epileptic patients, depth-EEG signals constitute a valuable source of information to characterize the spatiotemporal organization of paroxysmal interictal and ictal activities, prior to surgery. However, interpretation of these very complex data remains a formidable task. Indeed, interpretation is currently mostly qualitative and efforts are still to be produced in order to quantitatively assess pathophysiological information conveyed by signals. The proposed EEG mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…While seizure prediction was not the focus of this work, the inhibitory time constant showed a transition about 40 seconds before the onset of the seizure indicating the potential of this approach for seizure forecasting. Frogerais et al (2007) also demonstrated the feasibility of a similar approach using sequential Monte Carlo nonlinear filtering. Other work by Freestone et al (2011) and Aram et al (2013) demonstrated techniques for determining connectivity parameters for neural field models that can also be used to monitor brain changes.…”
Section: Model-based Inference Of Physiological Changes Underlying Epmentioning
confidence: 93%
“…While seizure prediction was not the focus of this work, the inhibitory time constant showed a transition about 40 seconds before the onset of the seizure indicating the potential of this approach for seizure forecasting. Frogerais et al (2007) also demonstrated the feasibility of a similar approach using sequential Monte Carlo nonlinear filtering. Other work by Freestone et al (2011) and Aram et al (2013) demonstrated techniques for determining connectivity parameters for neural field models that can also be used to monitor brain changes.…”
Section: Model-based Inference Of Physiological Changes Underlying Epmentioning
confidence: 93%
“…These computer simulations underscore the hypothesis that this form of epileptic seizures are caused by a gradual change in some parameters that are crucial for the control of the dynamical state of underlying neuronal network activity. Currently, the same model is being investigated further in the sense of attempting to solve an inverse problem, i.e., to identify the set of model's parameters based on observed EEG signals recorded at different stages, interictal, preictal, at seizure onset and during a seizure [24].…”
Section: A the Need For Computational Neurosciencesmentioning
confidence: 99%
“…The log-likelihood, p ( y :θ), is obtained using different approaches. [ 68 ] For example the model output is analytically a Markov process, so that the likelihood can be approximated by using the optimal filter or Kalman Filter. Optimization of the obtained likelihood is conducted by using the simulated annealing technique.…”
Section: Identification Of Depth-electroencephalogram Modelsmentioning
confidence: 99%